Anti-seepage steel breathable element and preparation method thereof
Through matrix pretreatment and particle-matrix interface treatment, submicron-scale pore structure and low expansion coefficient Al2TiO5 phase are formed, which solves the problem of traditional breathable brick argon blown channels being susceptible to penetration of steel, and significantly improves the strength, thermal shock resistance and penetration resistance of the breathable element.
Patent Information
- Application Number
- CN202510083146.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
AI Technical Summary
The argon blowing channel of traditional ladle breathable bricks is susceptible to penetration of steel, resulting in blockage of the channel and affecting the argon blowing effect of ladle refining.
The matrix pretreatment and particle-matrix interface treatment are used to fill the micropowder pores with α-cyclodextrin to form a submicron-scale pore structure. The titanium oxide fine powder is enriched on the surface of the complex phase corundum by adjusting the mixing process, and the Al2TiO5 phase with a low expansion coefficient is generated in situ to promote the connection between particles and the matrix and reduce interface gaps.
It significantly reduces the porosity of the breathable element, improves its strength, thermal shock resistance and water penetration resistance, and extends its service life.
Smart Images

Figure CN119841663A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to an anti-seepage steel permeable element which can be used for permeable bricks of a refining ladle and a preparation method thereof. Background Art
[0002] As a key functional refractory material for ladle refining and argon blowing, air bricks are used. During the refining of molten steel, argon is blown into the molten steel through the air bricks, driving the circulation of the molten steel and homogenizing the composition and temperature of the molten steel. However, after the refining and argon blowing is completed, the gas source pipeline is cut off, and the high-temperature molten steel will penetrate into the air brick along the argon blowing channel, resulting in blockage of the channel during the next refining and argon blowing. At present, the commonly used ladle air bricks at home and abroad are made of cement combined with corundum spinel castables, which are cast and sintered at high temperature before use. Because of the casting molding, the moisture in the castable forms a large number of large-sized pores. At the same time, it is difficult to sinter at high temperature between the matrix fine powder and the aggregate particles in the castable, forming a large number of gaps. As a result, the argon blowing channel of the castable air brick is very easy to penetrate the molten steel, resulting in the failure of ladle refining and argon blowing.
[0003] The patent specification with the publication number CN117962072A discloses a method for preparing a fired integral machine-pressed breathable functional element, wherein the breathable functional element is in the shape of a cylinder or a cuboid, and the outer periphery is a steel sleeve made of heat-resistant steel. The breathable functional element body formed by integral machine-pressing is combined with a casting material and a steel sleeve to form a high-strength and high-temperature-resistant breathable functional element; the preparation thereof comprises the following steps: step 1, preparing ingredients: preparing ingredients according to the raw material components and their weight proportions of the breathable element body; step 2, premixing: mixing the fused white corundum or plate-shaped corundum, alumina powder, zirconium material, and fused molybdenum weighed in the previous step; The raw stone is added into a vibrating ball mill for premixing, and the mixing time is 20 to 30 minutes; Step 3, stirring, granulating and screening: After adding certain additives and binders to the above-mentioned fine-grained powder, stir it in an adjustable-speed mixer for several minutes, and then use a 2mm sieve to screen out the agglomerated mud; Step 4, trapped material: After screening, the mud with uniform and fine particles is trapped for 24 hours, and its humidity is detected to be between 0.5 and 1.5%, and subsequent machine pressing molding is carried out; Step 5, brick preforming: a number of combustible polyester strips are evenly distributed at the preset positions in the mold, and the polyester strips run through the mold and vertically. Arranged in the same direction, and with polyester strip fixing plates on the upper and lower sides, the mud material in the previous step is placed in the mold for vibration, and the two ends are pressed by the machine. After the vibration machine is pressed into shape, the mold is removed and the preformed brick blank is taken out; Step 6, secondary molding: the preformed brick blank is placed in an isostatic press or an electric screw brick press for high-pressure molding through a prefabricated mold. The press adopts a large-tonnage brick press of more than 1,000 tons; Step 7, drying: the brick blank with higher strength in the previous step is placed in a drying kiln at 100-200°C for curing and drying for 24-48 hours; Step 8, high-temperature firing: the dried secondary molded brick blank is placed at 14 The brick is fired at a high temperature of 100-1700℃ in a high-temperature tunnel kiln or shuttle kiln, and the combustible polyester strips set inside the brick disappear, forming a reserved complete slit; Step 9, grooving: After firing, a grinder or a carving knife is used to cut a number of transverse grooves on the outer wall of the cylinder or rectangular block of the brick, which plays a role in preventing the breathable element from falling off during subsequent processing and use; Step 10, installing a steel sleeve: a steel sleeve is made according to the shape of the fired brick, and a gap is reserved on the steel sleeve to facilitate the passage of high-pressure gas along the gap. The high-temperature resistant steel sleeve is welded and wrapped around the outside of the machine-pressed breathable element body to form a complete breathable functional element that can be installed on site.
[0004] Before proposing the present invention, the applicant first proposed an invention patent application with publication number CN115572156A, which disclosed an aluminum-silicon-chromium gas-permeable element that is not wetted by molten steel and a preparation method thereof. The aluminum-silicon-chromium gas-permeable element includes a plate-shaped body, which is obtained by machine pressing from the following raw materials in mass percentage, and a serrated ventilation structure is provided: 51% to 72% of complex phase corundum particles, 1% to 10% of zirconium corundum, 7% to 18% of mullite particles, 10% to 20% of alumina micropowder, 1% to 6% of chromium oxide micropowder, and 1% to 3% of binder. This patented technology does not use cement, and the molding method is machine pressing. The matrix fine powder part is a relatively pure alumina mono-system, which greatly reduces the generation of low-melting phases in the gas-permeable element at high temperature and has a significantly lower porosity. The breathable element has high strength and excellent thermal shock stability and resistance to molten steel infiltration, which solves the problems of poor thermal shock stability of traditional breathable bricks, which leads to brick core fracture and restricts service life, and slit blockage caused by molten steel infiltration, which makes bottom blowing of breathable bricks impossible.
[0005] After extensive research, the applicant proposes a new anti-seepage steel breathable element and a preparation method thereof. The anti-seepage steel breathable element has lower apparent porosity, higher strength, stronger thermal shock resistance, and stronger ability to resist molten steel penetration. Summary of the invention
[0006] In order to solve the problem that the argon blowing channel of traditional breathable bricks is easily blocked by molten steel penetration, the present invention provides an impermeable steel breathable element and its preparation method, adopts a matrix (alumina micropowder, chromium oxide micropowder and α-cyclodextrin) pretreatment method, and uses the unique cavity structure of α-cyclodextrin to fill the micropowder pores, so that a large number of submicron pore structures are formed after the dense matrix is partially sintered at high temperature. At the same time, by adjusting the mixing process, the titanium oxide micropowder is enriched on the surface of the particles. During the high-temperature sintering process, the Al2TiO5 phase with a low expansion coefficient is generated in situ on the surface of the complex phase corundum particles, which not only has good thermal shock stability, but also promotes the connection between the particles and the matrix, significantly reduces the gap between the particles and the matrix interface, and significantly improves the strength, thermal shock resistance and resistance to molten steel penetration of the breathable element. After stacking and assembling, the breathable element is used for ladle refining breathable bricks, which has a good blowing rate and service life.
[0007] [1] An impermeable steel breathable element, comprising a body;
[0008] In parts by weight, the raw material composition of the main body includes: 65-85 parts (e.g., 78 parts) of complex phase corundum, 10-30 parts (e.g., 15 parts) of aluminum oxide powder, 0-6 parts of chromium oxide powder, preferably 0.5-6 parts (e.g., 1 part, 3 parts), 0.5-5 parts (e.g., 1 part, 3 parts), 0.5-2 parts (e.g., 1 part) of α-cyclodextrin, and 1-5 parts (e.g., 2 parts) of a binder;
[0009] The preparation method of the body comprises:
[0010] The binder is divided into a first part of the binder and a second part of the binder, wherein the first part of the binder is 30% to 50% (e.g., 40%) of the total weight of the binder, and the second part of the binder is 50% to 70% (e.g., 60%) of the total weight of the binder;
[0011] Alumina micropowder, chromium oxide micropowder that can be optionally added (i.e., not added when the weight portion of chromium oxide micropowder is 0, and added when the weight portion is not 0), α-cyclodextrin, and the first part of the binder are stirred and mixed, and under the action of the first part of the binder, the pores of the micropowder are filled with the unique structure of α-cyclodextrin so that a large number of submicron-level pore structures are formed after high-temperature sintering, thereby obtaining a first component;
[0012] The complex phase corundum is firstly stirred and mixed evenly with the second part of the binder, and then titanium oxide micropowder is added. Under the action of the second part of the binder, the titanium oxide micropowder is enriched on the surface of the complex phase corundum to form a titanium oxide micropowder coating structure, thereby obtaining the second component;
[0013] The first component and the second component are mixed and trapped, then subjected to machine pressing and high-temperature sintering at 1500-1700° C. and processed to form ventilation grooves to obtain the main body.
[0014] The present invention adopts the method of matrix pretreatment and particle-matrix interface treatment to make α-cyclodextrin evenly mixed in the matrix micropowder, and uses the unique structure of α-cyclodextrin to fill the micropowder pores, and after sintering, a large number of submicron pore structures (such as Figure 1 ), which improves the thermal shock resistance of the matrix part. At the same time, during the stirring process, titanium oxide powder is enriched on the surface of the complex phase corundum. During the high-temperature sintering process, the surface of the complex phase corundum particles and titanium oxide in situ generate Al2TiO5 phase with low expansion coefficient, which has good thermal shock stability, while promoting the connection between particles and the matrix, and reducing the large gaps formed at the interface between particles and the matrix. Compared with traditional casting materials, there are no large pores in the matrix, and a submicron pore structure is formed at the same time, which improves the thermal shock resistance of the material while reducing the porosity. By intervening in the particle-matrix interface reaction, the particle-matrix interface gap in traditional materials is significantly reduced, and the resistance to molten steel penetration is improved.
[0015] In some embodiments, the raw material composition of the body of the impermeable steel breathable element does not contain calcium aluminate cement.
[0016] In some embodiments, the total weight of the anti-seepage steel breathable element, the complex phase corundum, the aluminum oxide powder, the chromium oxide powder, the titanium oxide powder, α-cyclodextrin and the binder may be 100 parts.
[0017] In some embodiments, in the impermeable steel breathable element, the main phases in the complex phase corundum are 75wt% to 95wt% of the corundum phase and 5wt% to 12wt% of the aluminum-magnesium spinel phase.
[0018] In some embodiments, in the impermeable steel breathable element, the Al2O3 content in the complex phase corundum is ≥94.0wt%, the MgO content is ≤5wt%, and the Al2O3+MgO content is ≥98.5wt%.
[0019] In some embodiments, the impermeable steel breathable element and the complex phase corundum may be a combination of particles and fine powder, and further, the particle size may be 5-0 mm.
[0020] In some embodiments, the impermeable steel breathable element and the alumina powder may include one or more alumina powders having a median particle size D50 of 0.5 to 1 μm, 1 to 2 μm, and 4 to 5 μm.
[0021] In some embodiments, in the impermeable steel breathable element, the chromium oxide powder Cr2O3 content is ≥98.0wt%, and the median particle size D50 is ≤10μm.
[0022] In some embodiments, in the impermeable steel breathable element, the median particle size D50 of the titanium oxide powder is ≤5 μm.
[0023] In some embodiments, the binder of the impermeable steel breathable element may include one or more of phosphoric acid, aluminum dihydrogen phosphate solution, PVA (polyvinyl alcohol) solution, phenolic resin, silica sol, and aluminum sol.
[0024] In some embodiments, the body of the impermeable steel breathable element may be in the shape of a plate.
[0025] In some embodiments, the number of the ventilation grooves in the impermeable steel breathable element may be 20 to 60.
[0026] In some embodiments, the ventilation groove of the impermeable steel breathable element may be a serrated square structure.
[0027] [2] The method for preparing the impermeable steel breathable element according to [1], comprising preparing a body;
[0028] The preparation method of the body comprises:
[0029] The binder is divided into a first part of the binder and a second part of the binder, wherein the first part of the binder is 30% to 50% of the total weight of the binder, and the second part of the binder is 50% to 70% of the total weight of the binder;
[0030] Alumina micropowder, chromium oxide micropowder which may be optionally added, α-cyclodextrin and the first part of the binder are stirred and mixed, and under the action of the first part of the binder, the pores of the micropowder are filled with the unique structure of α-cyclodextrin so that a large number of submicron-level pore structures are formed after high-temperature sintering, thereby obtaining the first component;
[0031] The complex phase corundum is firstly stirred and mixed evenly with the second part of the binder, and then titanium oxide micropowder is added. Under the action of the second part of the binder, the titanium oxide micropowder is enriched on the surface of the complex phase corundum to form a titanium oxide micropowder coating structure, thereby obtaining the second component;
[0032] The first component and the second component are mixed and trapped, then subjected to machine pressing and high-temperature sintering at 1500-1700° C. and processed to form ventilation grooves to obtain the main body.
[0033] In the preparation method of the main body of the present invention, the time of trapping the material can be 24 hours.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The material of the air-permeable element disclosed in the present invention is different from the traditional air-permeable brick material. No calcium aluminate cement is added. The matrix part adopts alumina micropowder and chromium oxide micropowder. After pretreatment, a large number of submicron pore structures are formed in the matrix after high-temperature sintering, which significantly reduces the large pores in the traditional air-permeable brick material and improves the thermal shock resistance of the matrix part. At the same time, the surface of the complex phase corundum is coated, and after high-temperature treatment, the Al2TiO5 phase with a low expansion coefficient is generated in situ at the interface between the complex phase corundum particles and the matrix, which has good thermal shock stability, and at the same time promotes the connection between the particles and the matrix, and reduces the large pore gaps formed at the interface between the particles and the matrix. However, there are a large number of gaps at the interface between the particles and the matrix of the traditional air-permeable brick material. These two factors give the air-permeable element good strength, thermal shock stability and resistance to molten steel penetration. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a microstructure photograph of the anti-seepage steel breathable element of Example 1. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. The operating methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The air permeable element bodies in the following examples are all plate-shaped bodies, and the ventilation grooves formed thereon are all serrated square structures.
[0038] Table 1 shows the raw material composition of the anti-seepage steel breathable element body of each embodiment.
[0039] Table 1
[0040]
[0041] In Table 1:
[0042] The main phases in the complex phase corundum are 75wt% to 95wt% of corundum phase and 5wt% to 12wt% of aluminum-magnesium spinel phase;
[0043] The Al2O3 content in the multiphase corundum is ≥94.0wt%, the MgO content is ≤5wt%, and the Al2O3+MgO content is ≥98.5wt%;
[0044] The median particle size D50 of alumina powder is 2 μm;
[0045] Chromium oxide powder Cr2O3 content ≥ 98.0wt%, median particle size D50 ≤ 10μm;
[0046] The median particle size of titanium oxide micropowder is D50≤5μm;
[0047] The binder is aluminum dihydrogen phosphate solution.
[0048] The preparation method of the anti-seepage steel breathable element body of each embodiment includes:
[0049] The binder is divided into a first part of the binder and a second part of the binder, wherein the first part of the binder is 40% of the total weight of the binder, and the second part of the binder is 60% of the total weight of the binder;
[0050] Alumina micropowder, chromium oxide micropowder, α-cyclodextrin and the first part of the binder are stirred and mixed, and under the action of the first part of the binder, the pores of the micropowder are filled with the unique structure of α-cyclodextrin so that a large number of submicron pore structures are formed after high-temperature sintering to obtain the first component;
[0051] The complex phase corundum is firstly stirred and mixed evenly with the second part of the binder, and then titanium oxide micropowder is added. Under the action of the second part of the binder, the titanium oxide micropowder is enriched on the surface of the complex phase corundum to form a titanium oxide micropowder coating structure, thereby obtaining the second component;
[0052] The first component and the second component are mixed and trapped for 24 hours, then subjected to machine pressing and high-temperature sintering at 1500-1700° C. and processed to form ventilation grooves to obtain a main body.
[0053] Comparative Example 1:
[0054] Compared with Example 1, the raw material composition of the air permeable element body of this comparative example is the same, and the difference lies in the preparation method. The preparation method of the air permeable element body of this comparative example is as follows: after mixing the complex phase corundum, aluminum oxide powder, chromium oxide powder, titanium oxide powder, and α-cyclodextrin, a binder is added, the mixture is mixed and then trapped for 24 hours, and then machine-pressed and sintered at a high temperature of 1500-1700° C. and processed to form a ventilation groove to obtain a body.
[0055] Comparative Example 2:
[0056] Compared with Example 1, the raw material composition of the air permeable element body of this comparative example does not contain α-cyclodextrin, and the amount of complex corundum is changed to 79 parts by weight. The preparation method of the air permeable element body of this comparative example is the same as that of Example 1, except that no α-cyclodextrin is added during the preparation of the first mud material.
[0057] Comparative Example 3:
[0058] Compared with Example 1, the raw material composition of the air permeable element body of this comparative example does not contain titanium oxide powder, and the amount of complex phase corundum is changed to 81 parts by weight. The preparation method of the air permeable element body of this comparative example is the same as that of Example 1, except that titanium oxide powder is not added during the preparation of the second mud material.
[0059] The test results of the air permeable element body properties of each embodiment and comparative example are shown in Table 2.
[0060] Table 2
[0061]
[0062] From the performance comparison of each example in Table 2, it can be seen that the apparent porosity of the impermeable steel breathable element body of the present invention is significantly lower, and the strength and thermal shock resistance are significantly better. Comparative Example 1 does not carry out targeted pretreatment of the aggregate and the matrix separately, but simply and directly blends them at one time. The obtained breathable element body not only has a significant decrease in strength, but also the thermal shock resistance is reduced from 31 fractures in Example 1 to 15 fractures. Comparative Example 2 does not add α-cyclodextrin. Compared with Example 1, the strength of the obtained breathable element body is not significantly different, but the thermal shock resistance is reduced from 31 fractures to 9 fractures. Comparative Example 3 does not add titanium oxide powder. Compared with Example 1, the strength of the obtained breathable element body is significantly reduced, and the thermal shock resistance is reduced from 31 fractures to 18 fractures.
[0063] Figure 1 The data show that a large number of submicron-sized pores exist in the material matrix of Example 1, indicating that the introduction of α-cyclodextrin forms a large number of micropores in the matrix after sintering, which can significantly improve the thermal shock stability of the material.
[0064] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. An anti-seepage steel breathable element, characterized in that: Including the body; In parts by weight, the raw material composition of the main body includes: 65-85 parts of complex phase corundum, 10-30 parts of aluminum oxide powder, 0-6 parts of chromium oxide powder, preferably 0.5-6 parts, 0.5-5 parts of titanium oxide powder, 0.5-2 parts of α-cyclodextrin, and 1-5 parts of a binder; The preparation method of the body comprises: The binder is divided into a first part of the binder and a second part of the binder, wherein the first part of the binder is 30% to 50% of the total weight of the binder, and the second part of the binder is 50% to 70% of the total weight of the binder; Alumina micropowder, chromium oxide micropowder which may be optionally added, α-cyclodextrin and the first part of the binder are stirred and mixed, and under the action of the first part of the binder, the pores of the micropowder are filled with the unique structure of α-cyclodextrin so that a large number of submicron-level pore structures are formed after high-temperature sintering, thereby obtaining the first component; The complex phase corundum is firstly stirred and mixed evenly with the second part of the binder, and then titanium oxide micropowder is added. Under the action of the second part of the binder, the titanium oxide micropowder is enriched on the surface of the complex phase corundum to form a titanium oxide micropowder coating structure, thereby obtaining the second component; The first component and the second component are mixed and trapped, then subjected to machine pressing and high-temperature sintering at 1500-1700° C. and processed to form ventilation grooves to obtain the main body.
2. The anti-seepage steel breathable element according to claim 1, characterized in that: The raw material composition of the body does not contain calcium aluminate cement; The total weight of the complex phase corundum, aluminum oxide micropowder, chromium oxide micropowder, titanium oxide micropowder, α-cyclodextrin and binder is 100 parts.
3. The anti-seepage steel breathable element according to claim 1, characterized in that: The main phases in the complex phase corundum are 75wt% to 95wt% of corundum phase and 5wt% to 12wt% of aluminum-magnesium spinel phase; The Al2O3 content in the multiphase corundum is ≥94.0wt%, the MgO content is ≤5wt%, and the Al2O3+MgO content is ≥98.5wt%; The complex phase corundum is a combination of particles and fine powder, and the particle size is 5-0 mm.
4. The anti-seepage steel breathable element according to claim 1, characterized in that: The alumina fine powder includes one or more of alumina fine powders with a median particle size D50 of 0.5 to 1 μm, 1 to 2 μm, and 4 to 5 μm.
5. The anti-seepage steel breathable element according to claim 1, characterized in that: The chromium oxide micropowder has a Cr2O3 content of ≥98.0wt% and a median particle size D50 of ≤10μm.
6. The anti-seepage steel breathable element according to claim 1, characterized in that: The median particle size D50 of the titanium oxide micropowder is ≤5 μm.
7. The anti-seepage steel breathable element according to claim 1, characterized in that: The binder includes one or more of phosphoric acid, aluminum dihydrogen phosphate solution, PVA solution, phenolic resin, silica sol, and aluminum sol.
8. The anti-seepage steel breathable element according to claim 1, characterized in that: The body is plate-shaped; The number of the ventilation grooves is 20 to 60; The ventilation groove is a sawtooth square structure.
9. The method for preparing an impermeable steel breathable element according to any one of claims 1 to 8, characterized in that: The method comprises preparing a body; The preparation method of the body comprises: The binder is divided into a first part of the binder and a second part of the binder, wherein the first part of the binder is 30% to 50% of the total weight of the binder, and the second part of the binder is 50% to 70% of the total weight of the binder; Alumina micropowder, chromium oxide micropowder which may be optionally added, α-cyclodextrin and the first part of the binder are stirred and mixed, and under the action of the first part of the binder, the pores of the micropowder are filled with the unique structure of α-cyclodextrin so that a large number of submicron-level pore structures are formed after high-temperature sintering, thereby obtaining the first component; The complex phase corundum is firstly stirred and mixed evenly with the second part of the binder, and then titanium oxide micropowder is added. Under the action of the second part of the binder, the titanium oxide micropowder is enriched on the surface of the complex phase corundum to form a titanium oxide micropowder coating structure, thereby obtaining the second component; The first component and the second component are mixed and trapped, then subjected to machine pressing and high-temperature sintering at 1500-1700° C. and processed to form ventilation grooves to obtain the main body.
Citation Information
Patent Citations
Aluminum-silicon-chromium breathable element not infiltrated by molten steel and preparation method of aluminum-silicon-chromium breathable element
CN115572156A
Method for preparing air-permeable functional element through integral firing mechanical pressing
CN117962072A